Gregory of Nyssa, Augustine of Hippo, and the Filioque - Lee, Chungman, (Vigiliae Christianae, Supplements ;, 2021)
In The Filioque Reconsidered , Chungman Lee offers a concise yet thorough evaluation of the contemporary discussion on the filioque and the remaining issues still at stake. Lee examines the trinitarian theologies of Gregory of Nyssa and Augustine of Hippo, as representative of, respectively, the eastern and western patristic traditions. He demonstrates that they share similar ideas on the monarchy of the Father and on the role of the Son in the procession of the Holy Spirit, notwithstanding their slightly different expressions and perspectives. As such, the present study seeks to work towards a common patristic foundation for reconciliation between East and West on the problem of the filioque .